A Distinctive Feature of the Poetry of the Poet (Based on the Poems of Munavvara Usmanova) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
this article is about the famous poet Munavvara Usmanova, who has a special place in Uzbekistan, "Qaldirg'och", "ona, sizsiz qiynalib qoldim", "bitta savob qildim", "Nega menga bunday dil berding, Egam", "Shukrona", "boryapman, onamni asrasin Xudo!", "Sening yiqilganing ko'rmayin, bolam"is notable for the fact that, in the example of his poems, the peculiarities of the poetry of the poet are subject to analysis.